Contemporary Indian legislation, 1951-1978 Legislation contemporaine relative aux indiens, 1951-1978 (Treaties and Historical Research Centre, Corporate Policy, Dep. of Indian and Northern Affairs, 1981)
Begins with the Indian Act of 1951, and includes amending Acts, Statutory Orders and Regulations and other related contemporary legislation